2011
DOI: 10.1007/s00442-011-2153-3
|View full text |Cite
|
Sign up to set email alerts
|

Nectar alkaloids decrease pollination and female reproduction in a native plant

Abstract: The evolution of floral traits may be shaped by a community of floral visitors that affect plant fitness, including pollinators and floral antagonists. The role of nectar in attracting pollinators has been extensively studied, but its effects on floral antagonists are less understood. Furthermore, the composition of non-sugar nectar components, such as secondary compounds, may affect plant reproduction via changes in both pollinator and floral antagonist behavior. We manipulated the nectar alkaloid gelsemine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
4
34
2
Order By: Relevance
“…Moreover, our observation of uninfected bees having reduced probability of visiting a second flower on stems with high nectar iridoid glycosides accords with previous studies that have demonstrated pollinator deterrence by nectar secondary metabolites (Detzel and Wink , Kessler et al. , Adler and Irwin , Manson et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our observation of uninfected bees having reduced probability of visiting a second flower on stems with high nectar iridoid glycosides accords with previous studies that have demonstrated pollinator deterrence by nectar secondary metabolites (Detzel and Wink , Kessler et al. , Adler and Irwin , Manson et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…; Hough et al . )], and is one of the highest known in plant species to date (London‐Shafir, Shafir & Eisikowitch ; Adler & Irwin , ; Boros et al . ; Manson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although no substantial pollinator richness declines were detected during these early time periods, local density declines or changes in their foraging behavior might have already occurred, preceding the richness declines detected later on (Fig. In addition, the time lag detected for insects could be a response to changes in resource quality (Adler and Irwin 2011, Hoover et al 2012, Nijssen et al 2017, as discussed below. This suggests a time-lag for pollinator richness changes in relation to plants.…”
Section: Effect Of Resource Preferences On Historical Patterns Of Biomentioning
confidence: 93%